Analisis Kepuasan Pasien Rawat Jalan Puskesmas Dringu Kabupaten Probolinggo - Ani Nuraini; Ida Nurmawati; Rossalina Adi Wijayanti; Ervina Rachmawati (Politeknik Negeri Jember, 2021)
Dringu Public Health Center, Probolinggo Region, has a vision to become a public health center with the optimal health services. It can be known from patient satisfaction assessment. So far, the patient satisfaction assessment has never been carried out in Dringu Public Health Center. The purpose of this study was to analyze the outpatient satisfaction of the Dringu Public Health Center, Probolinggo Region, through service quality method based on five (5) service quality dimensions of tangible, reliability, responsiveness, assurance and empathy. This type of research used a quantitative method. The populations consist of 23526 peoples and the samples were 100 respondents. The sampling technique used purposive sampling.Â Data were collected by questionnaire. The results showed that the percentage of services in tangible dimension were 86.3% of patient satisfaction and 13.7% of patient dissatisfaction. The percentage of services in reliability dimension were 89.6% of patient satisfaction and 10.4% of patient dissatisfaction. The percentage of services in responsiveness dimension were 69.7% of patient satisfaction and 30.3% of patient dissatisfaction. The percentage of services in the assurance dimension were 68.2% of patient satisfaction and 31.8% of patient dissatisfaction. In the empathy dimension, the percentage of service were 74.1% of patient satisfaction and 25.9% of patient dissatisfaction. It is recommended to create a patient admission flow as well as create a service schedule poster for Dringu public health center.